2019
DOI: 10.26719/emhj.19.022
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among high school students in Erbil City, Iraq: prevalence and potential contributing factors

Abstract: Background: Substance use among adolescents, especially smoking and alcohol consumption, has become a public health concern in the Kurdistan Region, Iraq, in the past 10 years. Aims: This study aimed to determine the prevalence of substance use and certain associated factors among high school students in Erbil City, Kurdistan Region, Iraq. Methods: A cross-sectional study was conducted using a multistage cluster sampling technique to collect a sample of 3000 students. A modified version of the School Survey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
7
8
0
Order By: Relevance
“…Being male was 3 times increased odds of substance use than being women. This nding was in line with several studies conducted elsewhere (5,11,30,31,39,12,19,23,(25)(26)(27)(28)(29). This could be because males are more likely to experiment with things in their life.…”
Section: Substance Use-related Pro Les Among User Respondentssupporting
confidence: 90%
See 1 more Smart Citation
“…Being male was 3 times increased odds of substance use than being women. This nding was in line with several studies conducted elsewhere (5,11,30,31,39,12,19,23,(25)(26)(27)(28)(29). This could be because males are more likely to experiment with things in their life.…”
Section: Substance Use-related Pro Les Among User Respondentssupporting
confidence: 90%
“…Besides, those individuals are more likely to become hopeless and depressed that prone them to experiment with substance to relieve their problem. Since an individual who had a feeling of hopelessness or sadness and depression are more likely to use the substance (26,29,39).…”
Section: Substance Use-related Pro Les Among User Respondentsmentioning
confidence: 99%
“…Studies conducted in Ghana also reported similar findings [ 10 , 11 ]. The social learning principle which emphasizes that individuals can learn bad behaviours from watching their peers [ 14 ] could explain the findings in the study. Also, as peers are important sources of social support and therefore, their pressure can be an enforcer for good and bad behaviour [ 14 ].…”
Section: Discussionmentioning
confidence: 97%
“…waterpipe smoking, alcohol consumption, and use of unprescribed tranquilizers, respectively [27]. The same study also identified that 34.3% of the adolescents reported using any of the substances sometimes during their lifetime [27].…”
Section: Plos Onementioning
confidence: 96%
“…waterpipe smoking, alcohol consumption, and use of unprescribed tranquilizers, respectively [27]. The same study also identified that 34.3% of the adolescents reported using any of the substances sometimes during their lifetime [27]. To this end, it can be noted that the diversity of substance use in a particular cohort (medical students, for instance) can vary across the cultures, used methodology, and other factors [28][29][30].…”
Section: Plos Onementioning
confidence: 96%